2023
DOI: 10.5194/cp-19-1061-2023
|View full text |Cite
|
Sign up to set email alerts
|

Deglacial and Holocene sea-ice and climate dynamics in the Bransfield Strait, northern Antarctic Peninsula

Abstract: Abstract. The reconstruction of past sea-ice distribution in the Southern Ocean is crucial for an improved understanding of ice–ocean–atmosphere feedbacks and the evaluation of Earth system and Antarctic ice sheet models. The Antarctic Peninsula (AP) has been experiencing a warming since the start of regular monitoring of the atmospheric temperature in the 1950s. The associated decrease in sea-ice cover contrasts the trend of growing sea-ice extent in East Antarctica. To reveal the long-term sea-ice history at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 132 publications
1
10
0
Order By: Relevance
“…This shift between communities and the time point of change is supported by a Latent Dirichlet allocation (LDA) and a Bayesian change-point model (Supplementary Figure 1). The increase in temperature from ice-core data (29), the decline in sea-ice biomarkers (11), and the decrease in abundance of sea ice-associated taxa are congruent with the onset of a warm period beginning with the termination of the ACR (Fig. 2).…”
Section: Phaeocystis Antarctica Dominates the Phytoplankton Community...mentioning
confidence: 71%
See 4 more Smart Citations
“…This shift between communities and the time point of change is supported by a Latent Dirichlet allocation (LDA) and a Bayesian change-point model (Supplementary Figure 1). The increase in temperature from ice-core data (29), the decline in sea-ice biomarkers (11), and the decrease in abundance of sea ice-associated taxa are congruent with the onset of a warm period beginning with the termination of the ACR (Fig. 2).…”
Section: Phaeocystis Antarctica Dominates the Phytoplankton Community...mentioning
confidence: 71%
“…Biogenic opal concentration in sediments is the most commonly used paleoproductivity and carbon export proxy (10). Studies have found a decline or stable low concentration of biogenic opal during the ACR (11), which is inconsistent with the assumption that diatom blooms in the Southern Ocean were of critical importance in the ACR CO 2 plateau (8). High Ba/Fe ratios may indicate organic carbon drawdown in the Southern Ocean (12) as barite (BaSO 4 ) can precipitate during phytoplankton blooms, which is linked to carbon precipitation (13), but records covering the ACR are lacking.…”
Section: Mainmentioning
confidence: 99%
See 3 more Smart Citations